BUDAYA POP DAN FEMINIS DALAM NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Inung Setyami (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
This study is a qualitative descriptive and the data source is novel Ronggeng Dukuh Paruk written by Ahmad Tohari. It takes the 2009 edition published by PT. Gramedia Pustaka Utama. The data were obtained thorough reading followed by taking notes of all novels related to the pop culture and feminism. The technique of analysis is done through 1) identification, 2) classification, 3) interpretation, and 4) inference. The results showed that Roggeng Dukuh Paruk entails : 1) control of men over women, namely control of women's productive power or labor, control of female reproduction, control over the determination of women's sexuality, and control of women's movements; 2) found depiction of female image, which Hollows calls a fake female image